Synthesis of Relativistic Wave Equations: The Noninteracting Case - Andrzej Okniński (Advances in Mathematical Physics)
We study internal structure of the Duffin-Kemmer-Petiau equations for spin 0 and spin 1 mesons. We show that in the noninteracting case full covariant solutions of the s=0 and s=1 DKP equations are generalized solutions of the Dirac equation.